The reaction of the organism judoka 12-13 years of specific training load - Romanenko V.A; Romanenko L.P; Mosenz V.A; Horyakov V.A; Sokolov V.Y; Ivanov S.D (Kharkov National Pedagogical University, 2010)
Information is presented about a spectrum and level of violation of homoeostatic constants of organism of judoists in reply to the specific loadings of training and competition character. Judoists are inspected 12-13 years (n = 44). Before and after training employment registered the indexes of the functional state of neuromuscular vehicle, to oxygen-transport system, neurodynamics, sensory systems and mental capacity. Training employment in the aerobic (57,1%), mixed (20,0%) and glicolic (22,9%) modes of энергообеспечения results in the different degree of fatigue in the executive and regulator links of the functional system of activity of young judoists.